The Effect of Nutrition Education on the Knowledge of Pregnant Women in Preventing 1000 HPK Stunting in Kertasari Urban Village - Anggraeni, Risma; Srinayanti, Yanti; Sukmawati, Ima; Roslianti, Elis; Sunarni, Neli; Litasari, Resna (LPPM STIKes Muhammadiyah Ciamis, 2025)
Purpose:The purpose of this study was to determine the effect of nutrition education on pregnant women’s knowledge regarding stunting prevention during the first thousand days of life (HPK 1000). Methods: This study employed a quantitative approach with a pre-experimental design using a one-group pre-test and post-test model. The research subjects consisted of 11 pregnant women selected through random sampling from a total population of 28 pregnant women in Kertasari Village. Results: The results showed that after the implementation of nutrition education, all respondents (100%) were classified in the good category of nutritional knowledge. This finding indicates an improvement in pregnant women’s understanding of nutrition and its role in stunting prevention. Conclusions: The conclusion of this study demonstrates that nutrition education has a positive impact on pregnant women’s knowledge related to stunting prevention. Adequate nutritional knowledge during pregnancy is an important factor in supporting optimal fetal growth and development and plays a significant role in preventing stunting during the first thousand days of life.